Change of antirretroviral therapy: ineffectiveness or insecurity? (Research, Society and Development, 2022)
The aim of the study was to analyze the changes in antiretroviral therapy in patients treated at a medicine dispensing unit in Fortaleza, Ceará. An observational, documentary, descriptive, retrospective study with a quantitative approach was carried out from January to May 2020. All HIV/AIDS patients, registered in the drug dispensing unit, aged 18 or over were included. years that made changes in antiretroviral therapy from January to December 2019. Users who changed units during this period were excluded. There was a predominance of males, aged between 31 and 40 years, brown, single, with education corresponding to high school to higher education, natives and coming from Fortaleza, with diagnosis time between 1 and 5 years. Twenty-four different combinations of antiretroviral therapy were recorded, the most used association being tenofovir, lamivudine and efavirenz. Of the reasons that led to the change in antiretroviral therapy, the incidence or risk of adverse drug reaction, beginning or end of pregnancy and facilitating adherence to treatment prevailed. Efavirenz was the main drug involved in suspected adverse reactions, followed by tenofovir. It is concluded that the data obtained helped to understand the profile of people living with HIV in a Medicine Dispensing Unit in Fortaleza and the causes for changing antiretroviral therapy.